Prevalence and factors associated with overweight and obesity among rural and urban women in Burkina Faso - Diendéré, Jeoffray (Pan Afr Med J, 2019)
INTRODUCTION: Low- and middle-income countries, including Burkina Faso, are facing increasing urbanization with health challenges related to nutrition transition that impact body weight change. This study reported the prevalence and factors associated with overweight/obesity among women living in rural and urban Burkina Faso. METHODS: We conducted a secondary analysis using data from the Burkina Faso 2013 WHO STEPwise survey. Data included socio-demographic, clinical (anthropometric, systolic/diastolic blood pressure (SBP/DBP), oral/dental symptoms), biological (total and high-density lipoprotein cholesterol and fasting blood sugar), and alcohol and tobacco consumption data. A total of 2191 participants with complete data were considered in the analysis. We categorized the 13 Burkinabe regions by urbanization rate quartiles. We then performed Student's t, chi-squared, and Fisher's exact tests and backward stepwise regressions. RESULTS: The overall prevalence of overweight/obesity was 19.6% (13.1% and 44% in rural and urban women respectively, p=0.0001). Common factors positively associated with overweight/obesity in both rural and urban women were being a resident of a region in the highest urbanization rate quartile, having a high level of total cholesterol (alone or via an interaction with age) and having a high DBP. In urban women only, overweight/obesity was also associated with a high SBP. CONCLUSION: The prevalence of overweight/obesity in urban women in Burkina was among the highest levels in urban sub-Saharan Africa and roughly mimicked the urbanization profile of the country. In overweight/obesity conditions, cardiovascular concerns, such as increase in total cholesterol and blood pressure, were objective, and the blood pressure increase was more severe in urban women than in rural women.